THE GENRE MODEL OF A SCIENTIFIC PAPER IN THE RUSSIAN AND ENGLISH LANGUAGES - Nataliya I. Kolesnikova; Yuliya V. Ridnaya (Высшее образование в России)
The paper considers a burning for young researchers question how to write a scientific paper in the Russian and English languages. Since the requirements, recommendations and guidelines on the scientific paper structure presented in scientific and academic literature are mainly miscellaneous and often controversial, the author proposes to solve the problem using an invariant "Intergenre model of scientific text" providing a writer with a universal and basic algorithm for text generating activity.